Strong association of glaucoma with atherosclerosis - Xianqin Song (Nature Portfolio, 2021)
Abstract Carbonic anhydrases (CAs) catalyze the synthesis of HCO3 - from H2O and CO2. The dysfunction of CAs leads to aqueous humor secretion and high intraocular pressure to cause glaucoma pathogenesis. Methazolamide (MTZ), a CA inhibitor, can effectively treat glaucoma by reducing aqueous humor secretion. We previously reported that carbonic anhydrase I (CA1), a CA family member, was highly expressed in atherosclerotic tissues of the aorta and stimulated atherosclerosis (AS) by promoting calcification. MTZ showed therapeutic and preventive effects on AS in a mouse model. The above findings suggest a relationship between AS and glaucoma. This study explored the possible association between AS prevalence and glaucoma prevalence and the therapeutic effect of MTZ on AS by analyzing medical records. Among 10,751 patients with a primary diagnosis of glaucoma, 699 (6.5%) were also diagnosed with AS. However, the incidences of AS in patients with keratitis and scleritis, which are also ophthalmic diseases, were 2.5% (206/8383 patients) and 3.5% (46/1308 patients), respectively. In the population without ophthalmic records, the AS prevalence was only 1.9% (99,416/5,168,481 patients) (all p values between each group were below 0.001). Among 152,425 patients with a primary diagnosis of AS, 1245 (0.82%) were also diagnosed with glaucoma. Among 199,782 patients with a primary diagnosis of hypertension (excluding AS), 1149 (0.57%) were diagnosed with glaucoma, and among 5,313,433 patients without AS or hypertension, 9513 (0.18%) were diagnosed with glaucoma (all p values between each group were below 0.001). Additionally, among 14 patients who suffered from both AS and glaucoma and were treated with MTZ to cure their glaucoma, 9 of them showed reduced low-density lipoprotein (LDL) levels, the main index of AS, within 3 months after medication use (2.81 ± 0.61 mmol/L vs. 2.38 ± 0.58 mmol/L, p = 0.039). The above findings demonstrated a strong relation between AS and glaucoma and suggested that AS patients with glaucoma were more likely to suffer from angle-closure glaucoma.